Chiral Supramolecular Nanotubes of Single‐Chain Magnets. (22nd November 2019) - Houard, Felix; Evrard, Quentin; Calvez, Guillaume; Suffren, Yan; Daiguebonne, Carole; Guillou, Olivier; Gendron, Frédéric; Le Guennic, Boris; Guizouarn, Thierry; Dorcet, Vincent; Mannini, Matteo; Bernot, Kevin
Abstract: We report a single‐chain magnet (SCM) made of a terbium(III) building block and a nitronyl‐nitroxide radical (NIT) functionalized with an aliphatic chain. This substitution is targeted to induce a long‐range distortion of the polymeric chain and accordingly it gives rise to chains that are curled with almost 20 nm helical pitch. They self‐organize as a chiral tubular superstructure made of 11 chains wound around each other. The supramolecular tubes have a 4.5 nm internal diameter. Overall, this forms a porous chiral network with almost 44 % porosity. Ab initio calculations highlight that each Tb III ion possesses high magnetic anisotropy. Indeed, notwithstanding the supramolecular arrangement each chain behaves as a SCM. Magnetic relaxation with both finite and infinite‐size regimes is observed and confirms the validity of the Ising approximation. This is associated with quite strong coercive field and magnetic remanence ( H c =2400 Oe M R =2.09 μB at 0.5 K) for this class of compounds. Abstract : Eine supramolekulare Anordnung von Einzelkettenmagneten (SCM) wird vorgestellt, die sich selbstorganisieren, um chirale supramolekulare Nanoröhren zu bilden, die das magnetische Verhalten beibehalten. Magnetische Relaxation wird sowohl im finiten als auch infiniten Regime beobachtet.